Prevalence of cardiac complications in perinatally acquired human immunodeficiency virus infection in children in Southern India: an observational study - Angadi, Shambu S.; Angadi, Chaitra; Wari, Prakash K. (International Journal of Contemporary Pediatrics, 2024)
Background: Human immunodeficiency virus (HIV) infection is a multisystemic illness that impacts most organ system, to investigate prevalence of cardiovascular abnormalities in children with perinatally acquired HIV infection. Methods: This observational study was conducted in a tertiary care centre in Southern India. HIV-positive children between the ages of 18 months and 15 years were included. Cardiac abnormalities were defined as abnormalities identified on 2D echocardiography and/or electrocardiogram. Results: The 73 children with HIV infection had their cardiac manifestations assessed. Median age of children was 8 years with 52% of female participants, 22 (30.13%) children had cardiac abnormalities, of which 5 (27.27%) were symptomatic. Overall, 21/22 (95.45%) children had abnormalities on their ECG, 16 (72.72%) had abnormalities on 2D echocardiography. Of these, we found that children with delayed diagnosis of HIV infection and with more advanced clinical and immunological staging in HIV are more prone to develop cardiac complications irrespective of antiretroviral therapy (ART). Conclusions: HIV-related heart involvement is not uncommon, rather occur subclinical. A decreasing CD4 count and worsening clinical status are associated with increased risk. Hence its crucial to screen the children, diagnose at the earliest and timely manage the complications appropriately for prevention of early mortality.